La Academia. - Drake, Amelia (Tres edades, 2016)
The Academy is the beginning of a modern classic in the line of the great sagas of adventure that has captivated thousands of readers. Twelve is twelve years old and has never left the orphanage Moser, on the outskirts of the great city of Danubia. He does not know who their parents and even has a name, just a number, Twelve, having been the orphan of his twelfth year. In Danubia there are eighteen academies: the Musicians and the Alchemists, that of the Scribes and the Servants ... The Twelve dream is to enter the Academy and become a waitress Servants perhaps responsible for receiving with impeccable guests in one of the mansions of the city uniform. After a strange entrance examination, it is time that Twelve out of the orphanage and realize his dream. But the carriage in which travels on the river just because of an explosion and she ends up in a very different academy that is not even on the records of the city: the Nineteenth Academy. In the great city of Danubia, on an uninhabited island, it is prohibited school that nobody knows hides. And Twelve has been chosen to be part of it.